2008
DOI: 10.1111/j.1095-8649.2007.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Species boundaries and evolutionary lineages in the blue green damselfishes Chromis viridis and Chromis atripectoralis (Pomacentridae)

Abstract: The blue green damselfishes were described as a complex of two species (Chromis viridis and Chromis atripectoralis), mainly based on the colouration of the pectoral fin base. In this study, the authors analysed the mitochondrial control region of 88 blue green damselfishes from Indonesia, the Philippines, Red Sea and the Great Barrier Reef. The phylogenetic analysis revealed four major monophyletic clades. Two clades included specimens of C. atripectoralis from the Great Barrier Reef and individuals of C. viri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…During glacial periods, global sea levels dropped and exposed the bulk of the shallow seabed in the SCS, forming temporary land bridges connecting mainland Asia with the three Sunda Islands (Sumatra, Borneo and Java; Voris, 2000; Sathiamurthy and Voris, 2006). This landmass likely acted as a strong physical barrier halting sea-drifted gene flow between the SCS and the Indian Ocean populations of S. caseolaris during Pleistocene, consistent with the differentiation mechanism suggested for other mangrove species (Ge and Sun, 2001; Liao et al, 2007; Huang et al, 2008; Urashi et al, 2013; Wee et al, 2015) and numerous marine organisms (Barber et al, 2000; Nelson et al, 2000; Crandall et al, 2008; DeBoer et al, 2008; Froukh and Kochzius, 2008). …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…During glacial periods, global sea levels dropped and exposed the bulk of the shallow seabed in the SCS, forming temporary land bridges connecting mainland Asia with the three Sunda Islands (Sumatra, Borneo and Java; Voris, 2000; Sathiamurthy and Voris, 2006). This landmass likely acted as a strong physical barrier halting sea-drifted gene flow between the SCS and the Indian Ocean populations of S. caseolaris during Pleistocene, consistent with the differentiation mechanism suggested for other mangrove species (Ge and Sun, 2001; Liao et al, 2007; Huang et al, 2008; Urashi et al, 2013; Wee et al, 2015) and numerous marine organisms (Barber et al, 2000; Nelson et al, 2000; Crandall et al, 2008; DeBoer et al, 2008; Froukh and Kochzius, 2008). …”
Section: Discussionsupporting
confidence: 79%
“…Indo-Australian Archipelago (IAA), which extends from the Malay Peninsula through Sumatra, Borneo and Java to Sulawesi and the island of New Guinea, has the richest biodiversity on the planet (Mora et al, 2003). Molecular phylogenetic and population genetic studies in many marine organisms have revealed strong genetic discontinuities between the bodies of water separated by IAA (McMillan and Palumbi, 1995; Williams and Benzie, 1998; Duda and Palumbi, 1999; Nelson et al, 2000; Kochzius et al, 2003; Froukh and Kochzius, 2008). Barber et al (2000) proposed a marine Wallace’s line according to the genetic breaks between populations from north and south of Flores and Java Seas, and suggested that Pleistocene glacial isolation acted as a driver of intra-species genetic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…2002), the sea horse species Hippocampus trimaculatus (Lourie et al . 2005), as well as the boring giant clam, Tridacna crocea (Kochzius & Nuryano 2008). The authors suggest that the separation of different seas during the Pleistocene lead to a genetic differentiation and diversification of lineages, as proposed by McManus (1985).…”
Section: Discussionmentioning
confidence: 99%
“…) and coral genera (Sheppard & Sheppard ; DiBattista et al . ), as well as genetic differentiation between populations of coral reef organisms (Froukh & Kochzius ; Nanninga et al . ; Giles et al .…”
Section: Introductionmentioning
confidence: 99%